Editorial: Deep-sea taxonomy a contribution to our knowledge of biodiversity - Brökeland, Wiebke; George, Kai Horst (Zootaxa, 2009)
It is with great pleasure that we finished the compilation of this, the second special volume on deep-sea taxonomy in the year commemorating Darwin (2009). It is exactly 150 years after the publication of Darwin’s most notable work “On the Origin of Species by Means of Natural Selection, or the Preservation of Favoured Races in the Struggle for Life”. This remains the basis of our understanding of the history and diversity of life, the latter of which is expressed by the immense number of species inhabiting our planet in past and present.